2020
DOI: 10.3389/fmicb.2020.554249
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Typing Reveals Clonality of Fluconazole-Nonsusceptible Candida tropicalis: A Study From Wuhan to the Global

Abstract: Candida tropicalis is a globally distributed human pathogenic yeast, and its increasing resistance to azoles makes clinical treatment difficult. In this study, we investigated the clinical features, azole resistance and genetic relatedness of 87 C. tropicalis isolates from central China and combined with the global database to explore the relationship between genetic information and fluconazole susceptibility. Of the 55 diploid sequence types (DSTs) identified by multilocus se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 44 publications
4
15
0
Order By: Relevance
“…Given isavuconazole shares more similar chemical structures with short-chained azoles, our and other reports [26] demonstrated good correlation between isavuconazole and fluconazole/voriconazole. This is of particular concern in view of the emerging pan-azole-resistant clone, CC3, in Asia [5,7,10,11]. As shown in this study, C. tropicalis isolates exhibiting cross-resistance between isavuconazole and other azoles were collected in 2017, while isavuconazole was introduced in Asia in 2019.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Given isavuconazole shares more similar chemical structures with short-chained azoles, our and other reports [26] demonstrated good correlation between isavuconazole and fluconazole/voriconazole. This is of particular concern in view of the emerging pan-azole-resistant clone, CC3, in Asia [5,7,10,11]. As shown in this study, C. tropicalis isolates exhibiting cross-resistance between isavuconazole and other azoles were collected in 2017, while isavuconazole was introduced in Asia in 2019.…”
Section: Discussionmentioning
confidence: 76%
“…The proportion of C. tropicalis among Candida species causing candidaemia are relatively high in tropical Asia and Latin America compared to other continents [2,3]. Azole-resistant C. tropicalis clinical isolates have emerged worldwide [4][5][6][7][8][9][10][11]. This has become particularly problematic in the Asia-Pacific region since 2010 [4,5,7,10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, empirical antifungal treatment with echinocandins or amphotericin B product in candidemia patients with risk factors for C. tropicalis infection is strongly recommended. In our study, most of the patients infected with fluconazole-resistant C. tropicalis did not have a history of azole exposure and they may be acquired from the environment [ 21 ]. Azoles have been used in agriculture in Thailand and the link between fluconazole-resistant Candida and environmental azole exposure needs to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The burden of antifungal-resistant Candida tropicalis in humans, animals, and the environment Recent evidence points out that there is an increasing prevalence of fluconazole and multidrug resistance among C. tropicalis recovered from humans (Favarello et al, 2021;Wang et al, 2021). In China, some centers report a prevalence of 20-50% of fluconazole non-susceptibility among C. tropicalis clinical isolates (Fan et al, 2019;Wang et al, 2020;Wang et al, 2021), while in Algeria and Japan, reports show that more than 30% of C. tropicalis bloodstream isolates are fluconazole-resistant (Megri et al, 2020;Khalifa et al, 2022). In Turkey, a recent multicentric study showed that over 10% of the bloodstream isolates collected from 2017 to 2019 are resistant to fluconazole (Arastehfar et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%